ChemInform Abstract: Group (III) Nitrides M[Mg2Al2N4] (M: Ca, Sr, Ba, Eu) and Ba[Mg2Ga2N4]—Structural Relation and Nontypical Luminescence Properties of Eu2+ Doped Samples. Issue 5 (February 2015) - Pust, Philipp; Hintze, Frauke; Hecht, Cora; Weiler, Volker; Locher, Andreas; Zitnanska, Daniela; Harm, Sascha; Wiechert, Detlef; Schmidt, Peter J.; Schnick, Wolfgang
Abstract The new compounds (V), (VIII), and (X) are characterized by powder and single crystal XRD, SEM, UV/VIS spectroscopy, and luminescence spectroscopy.